Development of Sophisticated Thinking Blending Laboratory (STB-LAB) to Improve 4C Skills for Students as Physics Teacher Candidate - Rena Denya Agustina; Riki Purnama Putra; Milla Listiawati (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
The 21st Century Learning is an increasingly interactive and attractive learning era. The learning process in the 21st century does not only focus on teaching and learning activities in the classroom and explaining theories. There need to be laboratory activities that help provide visuals to students, especially future physics teacher candidates. Various innovations have been made in the development of laboratory activity models. There are still many laboratory activity models that focus on one activity, namely real or virtual. Laboratory activities in the 21st century do not always have to focus on super skills or 4C skills currently in the spotlight and forget about analytical skills and the balance between LOTS and HOTS. This study aims to develop a mixed laboratory activity model that can build 4C skills focused on analytical skills and balance between LOTS-HOTS; in addition, two activities are combined into one, real and virtual. The method used in this research is in the form of Research and Development using the ADDIE model with three meetings in implementation. The results obtained in this study, namely STB-LAB, obtained good model and guide validity results. N-Gain data showed that in the control class, only creative thinking skills were compelling enough, with a value of 59.47. In contrast, in experiment class, only communication skills have an effective enough category with a value of 57.84, but other aspects have an effective category with a value > 76.00. The hypothesis test showed that using STB-LAB could improve students as physics teacher candidate 4C Skills.